Mehmed Senai: A Crimean Historian at Sarai of Khan Islam Giray » - Refat Rustem ogly Abduzhemilev (Золотоордынское обозрение)
The article is devoted to the creative work of Mehmed Senai – the Crimean chronicler at the serai of the khan Islam Geray III, as well as his chronicle “Tarih-i Islam Geray khan” (“History of the khan Islam Geray III”, 1651). The researcher gives biographical information about the author and a brief description of the source. The identity of the writer is defined and based on the text of the Preface to the Chronicle: background, education, position, religious status. The meaning of the pseudonym of Senai is under the study, the text of the chronogram in which it occurs is reproduced. Especially noted thing is the originality of the artistic structure of the Chronicle “Tarih-i Islam Geray khan”.The Chronicle “Tarih-i Islam Geray khan” is the panegyric to the Crimean khan Islam Geray whose reign represents the brilliant epoch in the history of the Crimean Khanate. The writing consists of the ceremonies of public appointments, episodes of military campaigns and making treaties, the text of khan Islam Geray’s pedigree (shejere), construction and repair of buildings. There is the brief information about the Chronicle and about M. Senai in “Catalogue of the Turkish Manuscripts in the British Museum” (1888). The primary work on writing was conducted by Polish orientalists who prepared the edition of the original text, its translation and processing, backed with comments. At the time of writing the Chronicle, Mehmed Senai was in his old age, he served as the kadi (religious judge). In his youth he worked as munshi (decorator of papers) in the khan’s office. He got education in the Ottoman Empire, and was engaged in the implementation of diplomatic correspondence. The prospect of identification of the author on the basis of other sources is important to clarify the hypothesis of identifying M. Senai with such Crimean Tatar author as Dzhanmuhammed. The Chronıcle’s plot consists of the diary notes on the military expeditions, eyewitness accounts (including those of the author). The author of the work focuses the historical events of 1648–1651 covering the Crimean Tatar-Ukrainian-Polish relations. The bulk of the official documents used by Senai was narrow. Details and brevity in the coverage of events indicates that certain materials were available to the author, while others were unavailable. The aesthetic peculiarities of the Chronicle are also notable as well as historical. The author created the vivid images of the central characters in the writing – Islam Geray, Sefer Gazi aga and Tugay bey. The work is characterized by the use of various expressive means for the purpose of idealization of the images and emotional perception of characters and events.